An investigation of premature fatigue failures of gas turbine blade. (January 2015) - Maktouf, Wassim; Saï, Kacem
Highlights: Investigation of the premature blade failure by mechanical, metallography and chemical analysis. Metallurgical characterization of blade material. Finite element analysis of the blade geometry. Identification of the steady-state stress concentration areas and the stress/strain values. Probable cause of failure and recommendations to mitigate such incidents. Abstract: A failure of a first stage compressor blade of a Gas Turbine Generator in a Gas Treatment plant caused severe mechanical damage to the compressor section and power supply troubles. In this paper, the blade failure is investigated by mechanical, metallography and chemical analysis. A finite element analysis is performed on the blade geometry to identify the stress concentration areas and the stress/strain values. The investigation outcomes provided the most probable cause of the premature blade failure and the recommendations to mitigate such incidents.